LAMC1 upregulation via TGFβ induces inflammatory cancer‐associated fibroblasts in esophageal squamous cell carcinoma via NF‐κB–CXCL1–STAT3. Issue 11 (22nd July 2021) - Fang, Lingling; Che, Yun; Zhang, Chaoqi; Huang, Jianbing; Lei, Yuanyuan; Lu, Zhiliang; Sun, Nan; He, Jie
Abstract : Cancer‐associated fibroblasts (CAF) are a heterogeneous cell population within the tumor microenvironment, and play an important role in tumor development. By regulating the heterogeneity of CAF, transforming growth factor β (TGFβ) influences tumor development. Here, we explored oncogenes regulated by TGFβ1 that are also involved in signaling pathways and interactions within the tumor microenvironment. We analyzed sequencing data of The Cancer Genome Atlas (TCGA) and our own previously established RNA microarray data (GSE53625 ), as well as esophageal squamous cell carcinoma (ESCC) cell lines with or without TGFβ1 stimulation. We then focused on laminin subunit gamma 1 (LAMC1), which was overexpressed in ESCC cells, affecting patient prognosis, which could be upregulated by TGFβ1 through the synergistic activation of SMAD family member 4 (SMAD4) and SP1. LAMC1 directly promoted the proliferation and migration of tumor cells, mainly via Akt–NFκB–MMP9/14 signaling. Additionally, LAMC1 promoted CXCL1 secretion, which stimulated the formation of inflammatory CAF (iCAF) through CXCR2–pSTAT3. Inflammatory CAF promoted tumor progression. In summary, we identified the dual mechanism by which the upregulation of LAMC1 by TGFβ in tumor cells not only promotes ESCC proliferation and migration, but also indirectly induces carcinogenesis by stimulating CXCL1 secretion to promote the formation of iCAF. This finding suggests that LAMC1 could be a potential therapeutic target and prognostic marker for ESCC. Abstract : Inflammatory cancer‐associated fibroblasts (iCAF) are known to promote tumor progression. In our study we investigated the role of TGFβ1 on iCAF formation in esophageal squamous cell carcinoma (ESCC). TGFβ1 upregulated LAMC1 expression by activating SMAD4/SP1, which was abrogated by a TGFβR1 inhibitor (SB505124). The proliferation and migration of tumor cells was promoted by LAMC1 via the Akt/NF‐κB/MMP9‐MMP14 pathway. Additionally, LAMC1 facilitated CXCL1 secretion by activating NF‐κB. Tumor‐secreted CXCL1 stimulated the formation of iCAF through CXCR2/pSTAT3, which was blocked by a CXCR2 inhibitor (SB225002). In summary, iCAF promoted ESCC progression by secreting pro‐inflammatory cytokines and chemokines.